Cost of Production for Processed Oranges Grown in Southwest Florida, 2016/17 - Ariel Singerman (EDIS)
This 5-page fact sheet written by Ariel Singerman and published by the UF/IFAS Food and Resource Economics Department summarizes the cost of production per acre for processed oranges grown in southwest Florida during the 2016/17 season. Typical users of the estimates include growers and consultants, who use them as a benchmark; property appraisers, who use them to compute the taxes for property owners; and researchers, who use the estimates to evaluate the economic feasibility of potential new technologies. http://edis.ifas.ufl.edu/fe1038